Cerebrospinal fluid markers and magnetic resonance imaging lesion volume predicting relapse in canine meningoencephalitis of unknown origin - Spohn, Franziska; Lesta, Gloria; Wang-Leandro, Adriano; Kajin, Filip; Volk, Holger A.; Nessler, Jasmin N. (Frontiers in Veterinary Science, 2026)
IntroductionMeningoencephalitis of unknown origin (MUO) is a potentially lethal neurological disease in dogs with a high relapse rate. Prognostic factors for relapse based on neurological examination, magnetic resonance imaging (MRI), or cerebrospinal fluid (CSF) examination are inconsistently reported.MethodsThis retrospective single center study included 35 dogs with MUO. Brain MRI, CSF findings, clinical signs at diagnosis and during follow-up MRI (routine or relapse-related) were analyzed. Lesion volumes were calculated using the Cavalieri method. Relapse predictors were evaluated for routine follow- up MRI examinations using logistic regression and ROC/AUC.ResultOnly higher CSF albumin (p = 0.0413) and lymphocyte proportion (p = 0.0288) at routine follow-up examination were predictive of future relapse. ROC analyses identified thresholds of 9.64 mg/dl for CSF albumin (AUC: 0.75; sensitivity 86.7%, specificity 61.1%) and 74.0% for CSF lymphocytes (AUC 0.76; sensitivity 66.7%, specificity 64.3%). Total lesion volume and volume of contrast-enhancing lesions decreased after treatment and increased again at relapse. Increased lesion volume or normal MRI on routine follow-up MRI did not reliably predict future relapse, although increased lesion volume in T1-weighted contrast enhancement and Fluid-attenuated inversion recovery (FLAIR) was observed at or after relapse. Lesion volume, lesion number, and lesion localization in different sequences was associated with neurodisability scale (NDS) and epileptic seizures.DiscussionIn this study, CSF albumin and lymphocyte proportion were identified as predictors of future relapse. Routine follow-up MRI was not predictive of future relapse, but useful for detection of an active inflammation.